Preparation and Photocatalytic Activity of ZnO/CdS Core/Shell Structure Nanopowders - Li, Yan; Zhu, Shaofeng; Xie, Wenjie; Lei, Cong; Zhang, Jian (Asian Journal of Chemistry, 2014)
Zinc oxide nanopowders were prepared by a polyacrylamide-gel method, ZnO/ZnS and ZnO/CdS core/shell structure nanopowders were prepared by ion-exchange method, respectively. The as-prepared samples were characterized by X-ray diffraction, high resolution transmission electron microscopy (HRTEM). The results indicate that the hexagonal phase CdS nanoparticles grow on the surfaces of Wurtzite structure ZnO particles to form core/shell structure. The photocatalytic activities of the ZnO/CdS core/shell structure nanopowders were evaluated by degradation of methyl orange under UV, solar light and solar-simulated light irradiation. The results show that ZnO/CdS core/shell structure nanopowders exhibit an appreciable photocatalytic property, especially under UV and solar light irradiation.